A Study on Intravenous Sedation Versus Inhalation Sedation - Eyman Mustafa Bakier; Elaya Omar Aqeel (Journal of Scientific and Human Dimensions, 2026)
Introduction: Anesthesia is the cornerstone of modern medical and surgical practice, playing a vital role in enabling a wide range of diagnostic, therapeutic and surgical procedures. The primary goals of anesthesia include inducing unconsciousness, relieving pain, memory loss, muscle relaxation, and maintaining physiological stability throughout the period around the surgery. With continuous advances in anesthesia drugs and monitoring techniques, the practice of anesthesia has evolved significantly, allowing for safer procedures and improved patient outcomes. Inhalation and intravenous anesthesia remain among the most widely used techniques worldwide. Aim of study: This study aims to provide a comprehensive comparison between inhalation and intravenous anesthesia, focusing on their mechanisms of action, clinical applications, advantages, disadvantages, and associated side effects. By analyzing and comparing these two techniques, the research seeks to enhance understanding among anesthesiologists and contribute to improving the quality of care. Methodology: This study utilized a descriptive-analytical approach. Data was collected through a structured questionnaire distributed to a sample of 60 anesthesia practitioners working in hospitals in Misrata. The methodology focused on analyzing demographic variables, clinical practices, and pharmacological choices among the participants to evaluate the preferences and protocols used in different surgical scenarios. Data was collected using a structured questionnaire covering clinical practices and drug evaluations during the period from December 2025 to February 2026. Results:  The results showed different preferences based on the clinical situation: short surgeries (less than 30 minutes): 45% of participants prefer intravenous anesthesia. Long surgeries (more than 3 hours): 55%prefer the combination of intravenous and inhalation anesthesia. Pediatric surgery: 31.7% prefer the combination of the two types, while 30%prefer inhaled anesthesia alone. Reasons for preference for intravenous anesthesia: “speed of initiation” was the main reason for 55% of participants. Reasons for preferring inhalation anesthesia: 38.3% considered the "speed of waking up" to be the main advantage. The most commonly used drugs: Induction: Propofol by 90%. Analgesia: Fentanyl by 83.3%. Maintenance: Isoflurane by 58.3%. Conclusion: In conclusion, strong alignment with modern global trends, highlighted by a clear preference for Propofol-based Total Intravenous Anesthesia (TIVA) in short procedures due to its rapid onset, and a balanced combined approach for complex surgeries. Furthermore, the significant shift away from Nitrous Oxide reflects a positive clinical evolution toward safer, modern volatile agents. However, the study uncovers critical operational challenges, including a prominent gap in protocol standardization and institutional resource limitations that directly restrict drug availability.
Keywords: Intravenous Anesthesia; Inhalational Anesthesia; Drugs; And Surgery